Security Analysis and Preserving Block-Level Data DE-duplication in Cloud Storage Services - Adithya, M.; Shanthini, B. (Journal of Trends in Computer Science and Smart Technology, 2020)
Secure information deduplication can altogether decrease the correspondence and capacity overheads in distributed storage benefits and has potential applications in our large information-driven society. Existing information deduplication plans are commonly intended to either oppose savage power assaults or guarantee the effectiveness and information accessibility, yet not the two conditions. We are additionally not mindful of any current plan that accomplishes responsibility, in the feeling of lessening copy data divulgence (e.g., to decide if plain-writings of two scrambled messages are indistinguishable). Right now, examine the three-level cross-space design and propose an effective and protection safeguarding huge information deduplication in distributed storage (from now on alluded to as EPCDD). EPCDD accomplishes both protection safeguarding and information accessibility and opposes beast power assaults. Plus, we consider the responsibility to offer preferable protection affirmations over existing plans. We at that point show that EPCDD beats existing contending plans, as far as calculation, correspondence, and capacity overheads. Additionally, the time unpredictability of copy search in EPCDD is logarithmic.
Keywords: Main memory; memory deduplication; memory segment; virtualization; and execution